Wedded to the cause : Ukrainian-Canadian women and ethnic identity, 1891-1991 - Swyripa, Frances, 1951- (Heritage., 1993)
Frances Swyripe here presents the interpretive study of women of Ukrainian origin in Canada. She analyses the images and myths that have grown up around them, why they arose, and how they were used by the leaders of the community.